PRMT5 Is Involved in Spermatogonial Stem Cells Maintenance by Regulating Plzf Expression via Modulation of Lysine Histone Modifications - Dong, Fangfang; Chen, Min; Chen, Min; Jiang, Lin; Shen, Zhiming; Ma, Longfei; Han, Chunsheng; Guo, Xudong; Gao, Fei (Frontiers in Cell and Developmental Biology, 2021)
Protein arginine methyltransferase 5 (PRMT5) catalyzes the formation of mono- or symmetric dimethylarginine residues on histones and non-histone substrates and has been demonstrated to play important roles in many biological processes. In the present study, we observed that PRMT5 is abundantly expressed in spermatogonial stem cells (SSCs) and that Prmt5 deletion results in a progressive loss of SSCs and male infertility. The proliferation of Prmt5-deficient SSCs cultured in vitro exhibited abnormal proliferation, cell cycle arrest in G0/G1 phase and a significant increase in apoptosis. Furthermore, PLZF expression was dramatically reduced in Prmt5-deficient SSCs, and the levels of H3K9me2 and H3K27me2 were increased in the proximal promoter region of the Plzf gene in Prmt5-deficient SSCs. Further study revealed that the expression of lysine demethylases (JMJD1A, JMJD1B, JMJD1C, and KDM6B) was significantly reduced in Prmt5-deficient SSCs and that the level of permissive arginine methylation H3R2me2s was significantly decreased at the upstream promoter region of these genes in Prmt5-deficient SSCs. Our results demonstrate that PRMT5 regulates spermatogonial stem cell development by modulating histone H3 lysine modifications.